Disseminated Nontuberculous Mycobacterial Infection Following Cerebral Shunt Infection Caused by Mycobacterium fortuitum: A Case Report and Literature Review - Toyama-Kousaka, Mio; Shinoda, Masahiro; Yoshida, Takushi; Fujisaki, Marino; Sato, Takashi; Morikawa, Miwa; Takahashi, Hidenori; Shimada, Nagashige; Takei, Hiroaki; Shinkai, Masaharu (Internal medicine (Tokyo, 1992), 2025)
A 64-year-old, previously healthy woman underwent repeated shunt removal and reinsertion for shunt dysfunction due to hydrocephalus. M. fortuitum was detected in the culture solution at the end of the removed lumboperitoneal shunt approximately one year before the diagnosis; however, the result was considered to represent environmental contamination. The patient was hospitalized because of a high-grade fever, and M. fortuitum was detected in two blood cultures and a cerebrospinal fluid culture. We diagnosed the patient with disseminated nontuberculous mycobacterial infection due to M. fortuitum and removed the ventriculoatrial shunt. Multiple antimicrobial agents (imipenem/cilastatin, linezolid, ciprofloxacin, and trimethoprim/sulfamethoxazole) were administered for approximately two months, and the symptoms improved.